Staggered Stacking Covalent Organic Frameworks for Boosting Cancer Immunotherapy - Zhang, Liang; Xiao, Yao; Yang, Qi‐Chao; Yang, Lei‐Lei; Wan, Shu‐Cheng; Wang, Shuo; Zhang, Lu; Deng, Hexiang; Sun, Zhi‐Jun (Advanced functional materials, 2022)
The synergistic efficacy of phototherapy and cancer immunotherapy is severely restricted by both the inherent photobleaching and aggregation‐caused quench (ACQ) defects of photosensitizers and the intrinsic antioxidant tumor microenvironment (TME), such as hypoxia and overexpressed glutathione (GSH). To address these issues, a novel porphyrin‐based staggered stacking covalent organic framework (COF), COF‐618‐Cu, is rationally designed as a reactive oxygen species (ROS) amplifier, owing to its excellent catalase‐like activity, COF‐618‐Cu is capable of consuming endogenous hydrogen peroxide to produce sufficient oxygen to alleviate the tumor hypoxia phenomena. Moreover the overexpressed intracellular GSH is also depleted to decrease the scavenging of ROS, due to the glutathione peroxidase mimic activity of COF‐618‐Cu. Mechanistic studies reveal that the unique staggered stacking mode between COF‐618‐Cu interlayers can effectively relieve both the photobleaching and ACQ effects that are inaccessible to commonly eclipsed COFs. These, combined with their excellent photothermal therapy performance, make COF‐618‐Cu favorable for inducing robust immunogenic cell death and remodeling TME to boost antitumor immunity. A novel staggered stacking covalent organic framework (COF)‐based photosensitizer, COF‐618‐Cu, is reported, which can simultaneously alleviate photobleaching and aggregation‐induced quench effects to achieve desirable phototherapy performance and further elicit robust immunogenic cell death to trigger a durable antitumor immune response for boosting cancer immunotherapy.